SOSIALISASI PENGISIAN PROFIL BELAJAR SISWA INKLUSIF DI SDN 1 DAN MI AL-FATHIYAH LENDANG ARA KOPANG LOMBOK TENGAH - Heri Hadi Saputra; Mansur Hakim; Lalu Hamdian Affandi; Husniati Husniati; Radiusman Radiusman (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2021)
Student learning profile is an instrument that can help teachers to identify learning difficulties experienced by students, especially those with functional barriers. Therefore, this activity aims to improve the ability of teachers in filling out student learning profiles to teachers at SDN Lendang Ara and SDN Jurit with a total of 20 participants. This activity was carried out using presentation, discussion, question and answer methods and group work. Through presentations and question and answer sessions the team provided a conceptual understanding of the nature of inclusive education in primary schools, the goals and benefits of inclusive education. The socialization of filling in the student learning profile instruments was guided through presentations and discussions between the team and the teacher. Teachers in groups accompanied by teams fill out student learning profile instruments to identify learning barriers experienced by students. This community service activity recommends that universities and the government be more intense in socializing inclusive education programs and holding capacity training for teachers to be able to present solutions for the learning of children with functional barriers